Validation of a short questionnaire to measure symptoms and functional limitations associated with hand‐foot syndrome and mucositis in patients with metastatic renal cell carcinoma. Issue 2 (12th October 2015) - Lai, Jin‐Shei; Beaumont, Jennifer L.; Diaz, Jose; Khan, Sadya; Cella, David
Abstract : BACKGROUND: Hand‐foot syndrome and mucositis/stomatitis are frequent adverse events (AEs) of treatment with tyrosine kinase inhibitors in cancer therapy. Quality‐of‐life instruments that measure the functional consequences of these AEs are needed to assess the impact of therapeutic interventions and to guide patient care. The Hand‐Foot and Mucositis Symptom and Impact Questionnaire (HAMSIQ [formerly the Supplementary Quality of Life Questionnaire]) was used in the COMPARZ trial (Pazopanib vs Sunitinib in the Treatment of Locally Advanced and/or Metastatic Renal Cell Carcinoma [national clinical trial no. NCT00720941]) and the PISCES study (Patient Preference Study of Pazopanib vs Sunitinib in Advanced or Metastatic Kidney Cancer [clinicaltrials.gov NCT01064310]) to assess mouth/throat and hand/foot soreness symptoms and subsequent limitations in patients receiving pazopanib or sunitinib for metastatic renal cell carcinoma. The objective of the current analysis was to validate the HAMSIQ using data from the PISCES study. METHODS: The HAMSIQ was administered in the PISCES study at baseline and every 2 weeks over two 10‐week periods to patients who were receiving pazopanib or sunitinib. Data from the first 10‐week period were used to assess the feasibility, validity, and responsiveness of the HAMSIQ. RESULTS: In total, ≥85% of 169 patients completed the HAMSIQ (excluding the item concerning days off work). Correlations among items within the same limitation subscale generally were high (Cronbach α ≥ .80). HAMSIQ limitation scores differentiated patients according to their baseline performance status and severity of soreness. Small‐to‐moderate correlations were observed for the symptoms/limitation scores and for changes from baseline scores between the HAMSIQ and the Functional Assessment of Chronic Illness Therapy fatigue survey. The HAMSIQ demonstrated responsiveness to changes in clinical status and the development of hand‐foot syndrome AEs over time. CONCLUSIONS: The HAMSIQ is a feasible, valid, reliable, and responsive instrument for assessing the impact of hand‐foot syndrome and mucositis in patients receiving tyrosine kinase inhibitors. Cancer 2016;122:287–295. © 2015 American Cancer Society . Abstract : The Hand‐Foot and Mucositis Symptom and Impact Questionnaire (formerly known as the Supplementary Quality of Life Questionnaire) is a valid, reliable, and feasible instrument for assessing the impact of hand‐foot syndrome and mucositis in patients with metastatic renal cell carcinoma who are receiving multitargeted tyrosine kinase inhibitors. The questionnaire demonstrates good internal consistency, successfully differentiates patients according to baseline clinical measures and across differing levels of soreness, and is responsive to changes in clinical status and to the development of adverse events over time.